TEACHING YOUNG LEARNERS BY NEW METHODS - Muxiddin Farzona; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article describes the teaching of foreign languages for younger students using new methods in schools. According to modern methodological science, the purpose of teaching a foreign language is the ability to use it in communication with other peoples. The changed requirements for language proficiency have determined new approaches to the selection of content and organization of material.